Characteristics Of Patients With Lymphoma Diagnosis At Gunung Jati Cirebon Hospital In 2022-2024 - Ziya Ulhaq; Asih Ambarsari; Nurbaiti (Indonesian Health Issue, 2026)
ABSTRACT Background: Lymphoma is a malignancy of the lymphoid system that can involve lymph nodes and extranodal sites and remains a public health problem with an increasing incidence. Data on the characteristics of lymphoma patients in regional hospitals are still limited. Objective: To describe the characteristics of patients diagnosed with lymphoma at Gunung Jati Regional Hospital, Cirebon. Methods: This was a retrospective descriptive study using medical record data of lymphoma patients treated at Gunung Jati Regional Hospital during the period 2022–2024. Total sampling was applied. The variables analyzed included age, sex, clinical manifestations, tumor location, histopathological and immunohistochemical findings, treatment, and recurrence. Results: Of the 90 patients, most were male and belonged to the older age group. The most common clinical manifestation was a lump or mass, with predominant extranodal involvement. Most patients were diagnosed with Non-Hodgkin Lymphoma, with Diffuse Large B-Cell Lymphoma as the most frequent immunohistochemical subtype. Chemotherapy was the most commonly administered treatment, and no recurrence data were found during the observation period. Conclusion: Lymphoma patients at Gunung Jati Regional Hospital, Cirebon, during 2022–2024 were predominantly older males with extranodal involvement and Non-Hodgkin Lymphoma, particularly Diffuse Large B-Cell Lymphoma. These findings are important as a basis for clinical mapping and planning of lymphoma services in regional hospitals.